Resilient Annular Finite-Time Bounded and Adaptive Event-Triggered Control for Networked Switched Systems With Deception Attacks - M. Sathishkumar (IEEE Access, 2021)
This paper investigates the annular finite-time bounded and adaptive event-triggered control problems of networked switched systems (SSs) with deception attacks. Initially, we consider an adaptive event-triggered strategy (AETS) for switched systems that, compared to traditional strategies, can reduce inessential transmission in a communication network. Concurrently, an event-triggered threshold is obtained from the proposed adaptive law so that the control system can dynamically maintain satisfactory system performance. Subsequently, we consider the security issue of the networked switched systems subjected to deception attacks occurring in a random way where the bounded malicious signals are introduced by adversaries. On the strength of the delay-dependent Lyapunov functional candidate and Wirtinger-based integral inequality, several criteria, which calculated in the form of linear matrix inequalities (LMIs), are obtained to ensure the annular finite-time bounded for switched systems with prescribed mixed $H_∞ $ and passivity. Ultimately, the feasibility of the proposed method is verified by simulations.